Ageing challenges in the construction sector - Koukkari, Heli; Sarvakanta, Leena (International Journal of Strategic Property Management, 2010)
Ageing population and ageing infrastructure are two significant socioeconomic challenges, and business opportunities, for the construction sector in Europe. Utilisation of ICT in daily living is one of the future technology drivers. The principles of the Design for All (universal design) help to develop the built environment and its technologies in such a way that cities will be pleasant and supportive places for everybody. This paper considers the potential of new types of services and networking, which are very much under development at the moment and also under lively debate. The cost‐effectiveness – and so the availability – of the home delivered services will be dependent on the accessibility of the urban areas.First Published online: 18 Oct 2010